2019
DOI: 10.1186/s41935-019-0153-3
|View full text |Cite
|
Sign up to set email alerts
|

“Doctor, please don’t say he died by suicide”: exploring the burden of suicide survivorship in a developing country

Abstract: Background: Annually, 800, 000 die from suicide worldwide. However, suicide is believed to be rare in our environment. Suicide causes significant life disruptions in people bereaved by it. These disruptions result from associated complicated grieving pattern characterised by stigma, feeling of shame, responsibility, guilt, etc. People therefore usually want to be certain that their relation indeed died from suicide. Being certain can in part help survivors achieve closure. A pathologist is often called upon to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Deaths by suicide are perceived as sinful, a taboo and caused by evil forces, so the family are often times stigmatised and denied social opportunities. 10 People prefer to hide the mode of death, declaring suicides as accidental deaths or as homicides. 10 11 Many of the reported cases rely on police and hospital records, neither of which are comprehensive and might have been influenced by the bereaved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deaths by suicide are perceived as sinful, a taboo and caused by evil forces, so the family are often times stigmatised and denied social opportunities. 10 People prefer to hide the mode of death, declaring suicides as accidental deaths or as homicides. 10 11 Many of the reported cases rely on police and hospital records, neither of which are comprehensive and might have been influenced by the bereaved.…”
Section: Introductionmentioning
confidence: 99%
“… 10 People prefer to hide the mode of death, declaring suicides as accidental deaths or as homicides. 10 11 Many of the reported cases rely on police and hospital records, neither of which are comprehensive and might have been influenced by the bereaved. 7 10 Suicide is still a crime in Nigeria according to section 327 of the country’s Criminal Code.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, bereaved families would often misreport the cause of death to avoid judgement and blame, as well as to spare discriminatory practices towards the body of the deceased and the family. An exploratory study by Ohayi 30 similarly found that bereaved suicide survivors would often deny and misreport suicide as cause of death because of fear of stigma. This misreporting contributes to underestimation of suicide statistics, especially those highlighted in LMICs 31…”
Section: Discussionmentioning
confidence: 99%
“… 7 Also, family members prefer not to disclose the mode of death, reporting suicides as accidental deaths or as homicides at the hospitals or police stations. 8 In Nigeria, methods of engaging in suicidal behavior among youths include the use of chemicals, self-cutting, burning with kerosene, hanging, and firearms. 9 – 11…”
Section: Introductionmentioning
confidence: 99%